Functional and anatomical alterations in bilateral vestibulopathy: A multimodal neuroimaging study and clinical correlation - Lee, Eek-Sung; Weon, Young Cheol; Kim, Ji-Soo; Lee, Tae-Kyeong; Park, Ji-Yun (Frontiers in Neurology, 2023)
Object To study multimodal neuroimaging study including resting state functional MRI (rs-fMRI), anatomical connectivity and brain morphology in patients with bilateral vestibulopathy (BVP) and relationship with clinical correlation. Methods Thirteen patients with BVP (7 women; mean age ± SD = 63.5 ± 14.7 years, 22–80 years) and eighteen age and gender-matched controls were compared rs-fMRI and anatomical MRI. Also, we analyzed the relationship between multimodal neuroimaging and Dizziness Handicap Inventory score (DHI), Vestibular Disorders Activities of Daily Living Scale (VDRL), Geriatric Depression Scale (GDS) and Hospital Anxiety and Depression Scale (HADS). Results Compared with controls, BVP patients showed decreased functional connectivity among the key nodes of the salience network, auditory (including vestibular) network, bilateral posterior parahippocampal gyri, bilateral paracingulate gyri, and right frontoparietal network, and the anatomical connectivity in the right cerebellum, corpus callosum tapetum, and left fornix. BVP patients showed decreased gray matter volume in the bilateral parahippocampal gyri, right precentral gyrus, anterior cingulate gyrus, and right middle temporal gyrus and increased gray matter volume in the right superior frontal gyrus compared with controls. Correlation analyses showed rs-fMRI and clinical variables showed no significant result. DHI correlated negatively with anatomical connectivity in the bilateral frontal parahippocampal cingulum, corpus callosum, right inferior fronto-occipital fasciculus, bilateral fornix, and gray matter volumes in the bilateral middle occipital gyri, right superior occipital gyrus, left angular gyrus, and right cuneus in BVP. VADL correlated negatively with Anatomical connectivity in the corpus callosum, bilateral fornix, bilateral cerebellum, bilateral superior and anterior thalamic radiation, right inferior fronto-occipital fasciculus, bilateral fronto-parietal cingulum, right dentatoruburothalamic tract and gray matter volumes in the right angular gyri, bilateral parahippocampal gyri, right middle temporal gyrus, right cuneus, bilateral inferior occipital gyri, left middle occipital gyrus, right superior frontal gyrus, left fusiform gyrus, bilateral caudate, left cerebellar crus, and bilateral calcarine gyri in BVP. Conclusions This study identified reductions in the volume of the hippocampus and alterations in functional and anatomical connectivity that concurs with previously established characteristics of BVP. The degree of disability can be inferred from the change in the connectivity and volume between vestibular cortical areas and their network.